Do we harm others even if we don't need to? - Cacault, M. Paula; Goette, Lorenz; Lalive, Rafael; Thoenig, Mathias (Frontiers in Psychology, 2015)
Evolutionary explanations of the co-existence of large-scale cooperation and warfare in human societies rest on the hypothesis of parochial altruism, the view that in-group pro-sociality and out-group anti-sociality have co-evolved. We designed an experiment that allows subjects to freely choose between actions that are purely pro-social, purely anti-social, or a combination of the two. We present behavioral evidence on the existence of "strong aggression" -- a pattern of non-strategic behaviors that are welfare-reducing for all individuals (i.e. victims and perpetrators). We also show how strong aggression serves to dynamically stabilize in-group pro-sociality.